Efektivitas Ekstrak Teh Hijau (Camellia sinensis L.) terhadap Penurunan Kadar Glukosa Darah Puasa Tikus Wistar (Rattus Norvegicus) yang di Induksi Aloksan - Hafshah Hafshah; Kristina Simanjuntak (Poltekkes Kemenkes Padang, 2020)
The sufferers of Diabetes Mellitus (DM) in Indonesia is the highest with fourth number in the world, with a mortality rate of 1.2 million in 2012. Because of it, DM research using antihyperglycemic green tea is needed. This study aims to determine the effectiveness of green tea extracts on decreasing fasting blood glucose (KGDP) levels in alloxan-induced white male Wistar rats. Samples were 30 male rats, aged 8-12 weeks, weight ± 200 grams. Rats were grouped into 6 groups with the first group (K1) as a control, the second group (K2) induced alloxan, the third group (K3) induced alloxan with glibenclamide, the fourth group (K4), the fifth group (K5), and the sixth group (K6) induced alloxan with green tea extract as the treatment with dose of green tea extract, 200 mg/kg, 400 mg/kg, and 800 mg/kg. The first, FBG level examination is done 3 days after induction of alloxan using a glucometer. Giving green tea extract was given for 16 days orally, then FBG level re-examined from the tail of rats. One Way ANOVA Test Results, there is the effectiveness of green tea extract on reducing FBG level (p = 0,000). The post hoc Bonferroni test showed that giving 800 mg/kg of green tea extract was the best dose in reducing KGDP close to normal (p = 0,000).